Cybernetic-Based Numeracy Empowerment for Secondary Mathematics Teachers: A Community Engagement Perspective - Annisa Prima Exacta; Muhammad Zain Musa; Erika Laras Astutiningtyas; Andhika Ayu Wulandari; Krisdianto Hadiprasetyo (Educate: Journal of Community Service in Education, 2024)
This article presents a community engagement-based research initiative aimed at enhancing numeracy competence among senior high school teachers in Indonesia through a cybernetic pedagogy framework. Conducted at SMA Negeri 1 Nguter, the program combined theoretical workshops, digital tool integration, and cross-disciplinary lesson design to empower teachers in embedding numeracy across various subjects. A mixed-methods approach—comprising pre- and post-tests, structured mentoring, classroom observations, and reflective journals—revealed significant improvements in teachers' conceptual understanding, pedagogical confidence, and instructional practices. The findings demonstrate that cybernetic-based teaching fosters interactive, data-driven learning environments and supports numeracy as a transversal 21st-century skill. This study contributes empirical insights into scalable, cross-national professional development models that can be adapted in resource-constrained educational contexts